Pengaruh Pendekatan Realistic Mathematics Education Berbantuan Media Konkret Terhadap Kemampuan Berpikir Kritis Peserta Didik - Lestari, Novi; Istiningsih, Siti; Syazali, Muhammad (Mataram University, 2024)
This research aims to determine the effect of the Realistic Mathematics Education approach assisted by concrete media on the critical thinking abilities of class IV students at SDN 39 Cakranegara in the 2023/2024 academic year. The research method used is a quantitative approach with a pre-experimental design with a one group pretest posttest design. The average pretest score was 45.67 and the average posttest score increased, namely 85.18. Data analysis techniques were carried out using hypothesis tests, and n-gain tests. Based on the research results, it shows that the Paired sample t-test with the help of SPSS 25.0 for Windows obtained a Sig (2-tailed) value of 0.00 < 0.05, where Ho was rejected and Ha was accepted. So it can be concluded that the Realistic Mathematics Education approach assisted by concrete media has an influence on the critical thinking abilities of class IV students at SDN 39 Cakranegara.